Meta-analytic approaches to determine gender differences for delayed healing in venous leg ulcers. (December 2016) - Tang, Xiao-Lei; Chen, Hong-Lin; Zhao, Fang-Fang
Objective: The aim of this analysis was to perform a meta-analysis evaluating gender difference of delayed healing risk in patients with venous leg ulcers. Methods: We searched the PubMed and Web of Knowledge from their inception to 4 July 2015. The meta-analysis of pooled odds ratio and 95% confidence interval for venous leg ulcers healing risk were calculated. Results: Twelve studies with 4453 patients were included in the meta-analysis. The pooled odds ratio for healing rate stratified by gender was 1.055 (95% CI 0.955–1.165; Z = 1.05, p  = 0.292) by fix-effects model. The Begg's test (z = 2.67, p  = 0.007), the Egger's test (t = 4.00, p  = 0.003), and asymmetric funnel plot suggested there was significant publication bias. Subgroup analysis showed the pooled odds ratios were 1.048 (95% CI 0.945–1.162; Z = 0.88, p  = 0.376) in prospective studies and 1.439 (95% CI 0.757–2.736; Z = 1.11, p  = 0.266) in retrospective studies. Sensitivity analyses by only pooled adjusted odds ratios showed the pooled odds ratio was 1.049 (95% CI 0.946–1.163; Z = 0.91, p  = 0.365), which indicated the results of meta-analysis were robust. Meta-regression analysis showed the healing rate odds ratio stratified by gender was not related with healing rate (t = 0.73, p  = 0.484). Conclusion: Our meta-analysis indicates that no gender difference existed for delayed healing in venous leg ulcers. Our results may be also useful in developing a risk score for failure of venous leg ulcers to heal.